Evaluation of Air Pollution Tolerance Index and Anticipated Performance Index of Selected Plant Species - Winifred Uduak Anake; Jacinta Eigbefoh Eimanehi; Conrad Asotie Omonhinmin (Indonesian Journal of Chemistry, 2019)
This study reports a combination of two indices, air pollution tolerance index (APTI) and anticipated performance index (API) as viable tools for selecting suitable plants for pollution abatement program. Leaf samples of 6 plant species; Mangifera indica, Araucaria heterophylla, Elaeis guineensis, Syzygium malaccense, Acacia auriculiformis, and Chrysophyllum albidium were collected from an industrial and academic areas at Ado-Odo, Ota, Nigeria; during the dry season of January to March 2018. Biochemical parameters; leaf-pH, relative leaf water content, total chlorophyll content, and ascorbic acid content were analyzed to compute the APTI values. Combined APTI, botanical and socioeconomic indices were graded to evaluate the API of the different plant species. The APTI for the species ranged between 4.79 and 10.7, ideal for sensitive species category (APTI < 11), and the plants are classified as bio indicators of air pollution. The API indicates Mangifera indica and Syzygium malaccense (API = 4) as good performers while Chrysophyllum albidum is a moderate performer (API = 3). The three tree species were identified as suitable green belt plants and thus valuable additions to the green belt development plant list in tropical Africa.